Awareness and Effects of Extension Services on the Adopt-A-Day Care School Program - Jocelyn S. De Vera (East Asian Journal of Multidisciplinary Research, 2023)
One of the primary programs of an academic institution is to come out  change  by enabling people in certain communities by way of Extension Services. This study assessed the Awareness and Effect of  Extension  Services  on the  Adopt-A-Day Care School Program  of the College of  Teacher  Education particularly the Bachelor of Elementary Education Program to the pupils of  Bolaney Child Development  Center in Bolaney,Alaminos City,Pangasinan, Philippines. The evaluation type of  research intends  to gain an understanding of the success and challenges that the implementer  of the Adopt-A Day Care School Programs faced so as to guide future activities. A total of 56  respondents particularly mothers, guardians,  daycare worker, elementary teachers, and barangay officers were utilized as respondents. Frequency counts ,percentages and weighted mean  were used as statistical tools. Results showed that extension activities such as providing big books, pop-up books, and providing instructional materials enhance knowledge and skills to the children of the development center. School plays and puppet shows which was conducted in partnership with the Office of the Vice-mayor and  City Library of Alaminos City and other officials boosted the confidence and alertness of the children. Meanwhile, the outreach programs, activities conducted by the  NGO’s partners during school opening and Christmas seasons were highly appreciated by the respondents.